2014
DOI: 10.1186/1471-2105-15-96
|View full text |Cite
|
Sign up to set email alerts
|

Quantum coupled mutation finder: predicting functionally or structurally important sites in proteins using quantum Jensen-Shannon divergence and CUDA programming

Abstract: BackgroundThe identification of functionally or structurally important non-conserved residue sites in protein MSAs is an important challenge for understanding the structural basis and molecular mechanism of protein functions. Despite the rich literature on compensatory mutations as well as sequence conservation analysis for the detection of those important residues, previous methods often rely on classical information-theoretic measures. However, these measures usually do not take into account dis/similarities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 69 publications
(110 reference statements)
0
14
0
Order By: Relevance
“…Only the non-binding sites of our training data are used to compute p nd . As we have seen in [32] and [36], transforming empirical amino acid distributions of MSA columns by a carefully designed doubly stochastic matrix is an effective way to integrate the binding site signals. To this end, we first set up a counting matrix C bind in a way similar to that of calculating the matrix C nd .…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Only the non-binding sites of our training data are used to compute p nd . As we have seen in [32] and [36], transforming empirical amino acid distributions of MSA columns by a carefully designed doubly stochastic matrix is an effective way to integrate the binding site signals. To this end, we first set up a counting matrix C bind in a way similar to that of calculating the matrix C nd .…”
Section: Methodsmentioning
confidence: 99%
“…They were the first using JSD in this context and stated its superiority. Gültas et al [32] showed that the Jensen-Shannon divergence in the context of quantum information theory is of remarkable power. These three articles encouraged us to use JSD in this study.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations